Environmental issues and anthropic pressures in coastal aquifers: a case study in Southern Latium Region - Sappa, Giuseppe; De Filippi, Francesco Maria; Ferranti, Flavia; Iacurto, Silvia (Acque Sotterranee - Italian Journal of Groundwater, 2019)
Saline intrusion is one of the main problems in the drinking water quality management, especially for those coastal areas in which urbanization is seriously increasing. In fact, in some countries with an extensive coastline, such as Italy, the high drinking water demand can lead to an uncontrolled groundwater exploitation of coastal aquifers. During summer 2017, a severe drought event affected the entire Italian territory, including the study area located in the southern part of Latium Region. In order to overcome future water crisis, the water-supply agency (Acqualatina S.p.a.) has planned the realization of a wellfield in the "25 Ponti Area", belonging to the Municipality of Formia and about 500 m far away from the coastline. From September 2017 to December 2017, Tulliola Well has been completed and used at increasing flow rates to monitoring the effects of groundwater exploitation on this karst coastal aquifer. The aim of this paper is to present the first results of the monitoring activities, carried out by the Department of Civil, Building and Environmental Engineering (DICEA) of Sapienza University of Rome, in order to evaluate the rate of groundwater salinization due to a possible seawater intrusion phenomenon in the study area.